Seven views of mind - Wallach, Lise.; Wallach, Michael A. (New York : Psychology Press, 2013)
"This book examines seven different answers to the question, "What are we talking about when we talk about the mind?" It begins by considering the dualistic view, frequently taken for granted by students, that words like "belief," "anger," and "jealousy" refer to a realm quite distinct from the physical world, and notes the difficulties associated with this view as well as why many find it compelling. The book then describes six further major views of mind alternative to dualism that have been developed by psychologists, philosophers, and neuroscientists: Some claim that such words are just about behavior. Some claim that such words are theoretical constructs, like "quarks" in physics. Some identify the mind with the brain. Or with a kind of program in the brain, like the software in a computer. Some think there is nothing to which such words refer. Some think mental talk reflects nothing but convention"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Consciousness; Psychology; Electronic books